The role of acupuncture in treating premature ejaculation and its probable neurobiological mechanism - Anmin Wang; Hao Wang; Dongyue Ma; Hongyuan Chang; Ziwei Zhao; Dicheng Luo; Fu Wang (Basic and Clinical Andrology)
Abstract Background Premature ejaculation (PE) is one of the most common diseases in andrology and leads to serious male sexual dysfunction. Although several targeted oral drug therapies are used to treat PE, they often face challenges related to imprecise targeting and adverse effects. Acupuncture has shown potential in prolonging ejaculation time and improving couples' sexual quality of life. This review aims to summarize the benefits of acupuncture in treating PE and explore its probable neurobiological mechanisms. Results The review included eight clinical trials involving 679 patients, of which 294 were treated with acupuncture. Furthermore, this review analyzed acupuncture points, needle retention time, treatment duration, and their probable neurobiological mechanisms. The proposed mechanisms include stimulating the frontal functional lobe, inhibiting spinal cord neural pathways, regulating serotonin levels, enhancing 5-hydroxytryptamine receptor IB excitability, reducing penile sensitivity, and modulating hormone levels. Conclusions Acupuncture is a viable alternative or complementary therapy for PE, and neurobiological mechanisms appear to play a key role, but further experimental validation is needed.